Pharmacokinetics and Pharmacodynamics of an Oral Formulation of Apixaban in Horses After Oral and Intravenous Administration - Serpa, Priscila B. S.; Brooks, Marjory B.; Divers, Thomas; Ness, Sally; Birschmann, Ingvild; Papich, Mark G.; Stokol, Tracy (Frontiers in Veterinary Science, 2018)
Horses with a variety of inflammatory and infectious disorders are often treated with injectable heparin anticoagulants to prevent thrombotic complications. In human medicine, a new class of direct oral acting anticoagulants (DOAC) appears to be as effective as heparin, while eliminating the need for daily injections. Our study in horses evaluated apixaban, a newly approved DOAC for human thromboprophylaxis that targets activated factor X (Xa). Our study goals were to: 1) Determine pharmacokinetics and pharmacodynamics of apixaban after oral (PO) and intravenous (IV) administration to horses; 2) Detect any inhibitory effects of apixaban on ex vivo EHV-1-induced equine platelet activation, and 3) Compare an anti-Xa bioactivity assay with ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) for measuring apixaban concentrations in equine plasma. In a blinded placebo-controlled cross-over study, 5 horses received a single dose (0.2 mg/kg) of apixaban or placebo PO or IV. Blood was collected before and at 3 (IV) or 15 (PO) minutes, 30 and 45 minutes, and 1, 2, 3, 4, 6, 8 and 24 hours after dosing for measuring apixaban UPLC-MS concentrations and anti-Xa activity. Pharmacodynamic response to apixaban was measured in a dilute prothrombin time (dPT) assay. Flow cytometric EHV-1-induced platelet P selectin expression and clinical pathologic safety testing were performed at baseline, 2 and 24 hours and baseline and 24 hours, respectively. We found no detectable apixaban after PO administration. After IV administration, plasma apixaban levels followed a two-compartment model, with concentrations peaking at 3 minutes and decreasing to undetectable levels by 8 hours. The elimination half-life was 1.3 ± 0.2 hours, with high protein binding (92-99%). The dPT showed no relationship to apixaban UPLC-MS concentration and no inhibitory effect of apixaban on EHV-1-induced platelet activation was seen after IV dosing. Apixaban anti-Xa activity showed excellent correlation to UPLC-MS (r2 = 0.9997). While no clinical, hematologic or biochemical changes were seen after PO or IV administration, apixaban has no apparent clinical utility as an anticoagulant for horses due to its poor oral availability.